Externalities, collective goods and the requirement of a state's intervention in pollution abatement - François Lévêque (Fondazione Eni Enrico Mattei (FEEM), 1997)
The concepts of externality and collective good are often used by economists to infer that a state's intervention is strictly necessary to cope with the harmful effects of pollution on the environment. Such inference is wrong. It is also misleading. An example is provided by the current debate on voluntary approaches in pollution abatement. These are self-regulatory arrangements where a firm or an industry association, commits in an environmental programme vis-à-vis consumers or local communities. A well-known example is the Responsible Care Programme undertaken by the International Council of Chemical Associations. Based on the common belief that a state's intervention is the single means to achieve pollution abatement, such initiatives are judged as reflecting a pure communication strategy and are expected to unavoidably result in cosmetic effects on the environment. The aim of the paper is to remind that the nature of hazardous emissions as externalities and the nature of their abatement as collective goods do not logically imply that a state's intervention is necessary in ensuring pollution reduction. The exclusion of private arrangements as an alternative to public regulation is not theoretically founded. The paper surveys the market failures theory revisionism as initiated by Coase (1960) and developed in the law and economics literature. It concludes that whether private arrangements in pollution abatement may be an alternative to public regulation is an issue which can only be treated and solved at the empirical level. The micro-economic rationale for public intervention in case of externality is discussed and criticised in section two, that one of collective good in section three.
Keywords: 330; Externer Effekt; Umweltbelastung; Öffentliche Güter; Marktversagen; Interventionismus; Theorie